BRAIN ARTERIOVENOUS MALFORMATION WITH ORBITAL INVOLVEMENT PRESENTING AS PROPTOSIS: A CASE REPORT - Trihardi, Rizfan; Ramadhani, Nur'aina Isna Dewi (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Brain arteriovenous malformation (AVM) is a rare vascular anomaly of the central nervous system that may present with headache, seizures, or focal neurological deficits. Orbital involvement leading to proptosis is extremely uncommon and may delay the diagnosis if not properly recognized. Case Report: A 35-year-old female presenting with chronic headache, focal seizures, left-sided hemiparesis, hemihypoesthesia, and progressive right eye proptosis. Neurological examination confirmed motor weakness and sensory impairment on the left side. Brain MRI and CT angiography revealed a large cerebral AVM with orbital venous drainage causing orbital congestion and proptosis. Discussion: AVM with orbital involvement is exceedingly rare, with only few cases described in the literature. Proptosis usually results from venous hypertension [A2.1][A2.2]secondary to abnormal arteriovenous shunting and orbital venous drainage. This unusual presentation poses diagnostic challenges, often mimicking orbital or ophthalmologic disorders. Recognition of the clinical spectrum is crucial to avoid misdiagnosis and ensure timely management. Conclusion: This case highlights the importance of considering cerebral AVM in the differential diagnosis of patients presenting with proptosis accompanied by neurological manifestations. Early identification and appropriate referral are essential to improve patient outcomes.